The Hydra of Tyranny, The Fall of Robespierre and the Early Demise of Robert Southey's Revolutionary Enthusiasm. Issue 2 (July 2019) - Taylor, Jonathan
Abstract : This article explores Robert Southey's pessimistic re-appropriation of the popular revolutionary symbol of the hydra in the closet drama The Fall of Robespierre (1794). Challenging the prevailing view that Southey was an enthusiastic revolutionary throughout the 1790s, the study progresses from an exploration of the hydra's ubiquitous use in revolutionary and loyalist propaganda to an account of Southey's damning re-appropriation of the monster as a symbol for recurrences of tyranny in France's revolutionary governments. Analyses of The Fall of Robespierre, Southey's closet drama Wat Tyler (1794) and epic Joan of Arc (1796) demonstrate that Southey acquired an early conviction that tyranny was a recurrent obstacle to democracy, which rendered revolution futile. Arguing that Southey's revolutionary zeal had largely abated by 1793, I contend that his youthful incredulity about the plausibility of establishing a republic informed, and constitutes a principled explanation for, his notorious apostasy and conservatism in later life.